Implementation of Merdeka Curriculum through Project-based Islamic Education Learning Model: Case Study at Madrasah Tsanawiyah (MTs) Hubbul Wathan Sangatta, Indonesia - Nurwati, Nurwati; Rachman, Muhammad Sultan Al Viqri; Pandiangan, Anjani Putri Belawati (Tinta Emas Institute, 2024)
Islamic religious education (PAI) at MTs Hubbul Waton has undergone changes with the implementation of the Merdeka Curriculum. This curriculum emphasizes students' ability to think critically, communicate effectively, and adapt to change. In an effort to improve the quality of PAI education, a project-based learning model is applied to integrate these abilities. The project aims to improve students' ability to think critically, communicate effectively, and adapt to change through the PAI approach. In this implementation, students are divided into groups and given tasks to develop projects related to PAI materials. The project includes analysis, synthesis, and evaluation of PAI materials, as well as communication of the results through presentations and discussions. Thus, students can develop the ability to think critically, communicate effectively, and adapt to change. The implementation results showed an increase in students' ability to think critically, communicate effectively, and adapt to change. Students also show high interest and motivation in developing PAI projects. Thus, the implementation of Merdeka Curriculum through a project-based PAI learning model at Hubbul Waton MTs can be considered successful in improving the quality of PAI education.